SEJARAH, UNSUR KEBUDAYAAN, DAN NILAI PENDIDIKAN KARAKTER DALAM LEGENDA SUNGAI NAGA - Suwarno Suwarno; Kundharu Saddhono; Nugraheni Eko Wardani (Universitas Negeri Makassar, 2018)
History, Cultural Elements, and the Value of Character Education in the Legenda Sungai Naga. The purpose of this study is to describe the history, elements of culture, and the value of character education on the Legenda Sungai Naga. Data collection through interviews, documentation, and observation. Data analysis technique used qualitative analysis of inductive model with purposive sampling technique. The results obtained that the name of the Dragon River taken based on the history of Gerdu figures that dispels the Dragon Snake that pass in the river. It found three elements of culture that is naming places, namely knowledge system, living equipment system and technology, and religious system. There are three values of character education that is the value of hard work character, religious character value, and value of environmental caring character.